2017
DOI: 10.1016/j.ab.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic behavior of laccase following interaction with γ-CD and immobilization into PCL nanofibers

Abstract: This study examines the effects of CD use on enzymatic activity, following enzyme immobilization into nanofibers. There is almost no research available on the change in enzyme activity following interaction with cyclodextrin and electrospun nanofiber mats together. Laccase enzyme was immobilized into nanofibrous structures by various techniques, with and without γ-CD addition, and the enzymatic activity of the laccase was analyzed. SEM, XRD, and FTIR analyses were used for the characterization of the resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The positive influence of CDs on enzyme activity and the stability of the catalase was showed. Similar to the catalase enzyme, laccase was immobilized on γ-CD/PCL nanofibers and showed higher catalytic activity (96.48 U/mg), compared to enzymes immobilized on PCL nanofibers without CDs (23.2 U/mg) or γ-CD/laccase physical mixtures in PCL nanofibers (71.6 U/mg) [75]. During the formation of the CD-enzyme complex, the enzyme used did not lose activity and no denaturation was observed.…”
Section: Polymeric Drug Delivery Systems From Cyclodextrin and Poly(εmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive influence of CDs on enzyme activity and the stability of the catalase was showed. Similar to the catalase enzyme, laccase was immobilized on γ-CD/PCL nanofibers and showed higher catalytic activity (96.48 U/mg), compared to enzymes immobilized on PCL nanofibers without CDs (23.2 U/mg) or γ-CD/laccase physical mixtures in PCL nanofibers (71.6 U/mg) [75]. During the formation of the CD-enzyme complex, the enzyme used did not lose activity and no denaturation was observed.…”
Section: Polymeric Drug Delivery Systems From Cyclodextrin and Poly(εmentioning
confidence: 99%
“…In addition, the CD enriched PCL fibers were used for encapsulation of small molecules like α-tocopherol [71], naproxen [72], sulfisoxazole [68], ciprofloxacin [73], as well as even large molecule (e.g., polymer or enzyme) [74,75,98,101,102]. Those studies were initiated to enhance the stability of active compounds against various environmental factors during delivery by entrapment them in PCL nanofibers.…”
Section: Polymeric Drug Delivery Systems From Cyclodextrin and Poly(εmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported that enzymes could be immobilized on various nanofibers made from cellulose polymers [15], polystyrene [7], poly(ε-caprolactone) [16], polyaniline [17], chitosan [18], polyethylene oxide [19], polylactic acid [20], and polyacrylonitrile [21]. Nanofiber is fabricated using an electrospinning device, and the size of fibrous mats ranges from nanometers to a few micrometres.…”
Section: Introductionmentioning
confidence: 99%
“…A critical challenge for enzyme immobilization is to develop high‐performance carriers . The characteristics of an ideal carrier for enzyme immobilization include inexpensive nature , being able to load a significant amount of enzyme per unit weight , low hydrophobicity , inertness after immobilization , microbial resistance , pH, thermal, and mechanical resistance . Conventionally, nanoparticles and microspheres have been used as carriers for immobilized enzymes because of their large specific surface area and porosity, resulting in higher enzyme loading of the immobilization process .…”
Section: Introductionmentioning
confidence: 99%